2021
DOI: 10.1080/1331677x.2021.1939089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of investment behaviour on financial markets during COVID-19: a case of UK

Abstract: This study aims to determine the impact of investment behavior on financial markets during COVID-19 with respect to the UK. This study is quantitative, where the data has been gathered from the primary sources of information, i.e., through a survey questionnaire. The researcher adopted the non-probability convenience sampling through which 337 responses were gathered. The questionnaire was self-administered, which was based on 7 points Likert scale. Concerning the analysis, the SEM technique has been adopted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Previous studies on financial decision-making claims that adopting a convenience sampling method allows a researcher to acquire relevant information that would be difficult to obtain using other probability sampling techniques. Moreover, given the context of Covid-19 pandemic restrictions, several studies do confirm the fact that convenience sampling method is one of the preferable methods of collecting data as the sampling is affected by the study's location and situation (Wang et al ., 2022; Gerth et al ., 2021). Hence, in light of the Covid-19 constraints, the current study adopts a convenience sampling approach in which a generic sample from the desired population is taken from a set of persons who are easy to contact or reach.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on financial decision-making claims that adopting a convenience sampling method allows a researcher to acquire relevant information that would be difficult to obtain using other probability sampling techniques. Moreover, given the context of Covid-19 pandemic restrictions, several studies do confirm the fact that convenience sampling method is one of the preferable methods of collecting data as the sampling is affected by the study's location and situation (Wang et al ., 2022; Gerth et al ., 2021). Hence, in light of the Covid-19 constraints, the current study adopts a convenience sampling approach in which a generic sample from the desired population is taken from a set of persons who are easy to contact or reach.…”
Section: Methodsmentioning
confidence: 99%
“…The sample sizes of 366, and 374 have been employed in previous studies for testing study models of 4–6 hypotheses ( Sumarliah et al, 2021a , b ). According to Fugard and Potts (2015) , the present study adopted the formula ( n = ) with identical parameters to determine the adequate sample size ( Fugard and Potts, 2015 ; Wang et al, 2022 ). Based on this equation, it can be determined that the adequate sample size for this study is 384.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is discovered that households' risk tolerance increases for the early stages of the COVID-19 pandemic by using an incentivized experiment (Shachat et al 2020), and it is found that there is no change in risk assessment in a risk elicitation task during the COVID-19 pandemic (Angrisani et al 2020). On the other hand, Wang et al (2021) found that COVID-19 uncertainty significantly moderates the relationship between risk perception and risk tolerance both generally and financially.…”
Section: Post-pandemic Risk Assessment In Household Cryptocurrency In...mentioning
confidence: 99%